Spatial identification of lost-and-found carbon hotspots at Javanese rice systems, Indonesia - Asmara, Degi Harja; Rala, Arnel; Batas, Mary Ann A.; Laborte, Alice; Flor, Rica J.; Khumairoh, Uma; Sembiring, Hasil; Yadav, Sudhir (Elsevier, 2024)
Agricultural landscapes play a crucial role in global carbon sequestration and biodiversity conservation. The presence of trees outside forests has been recognized as a significant carbon pool, but it is crucial to acknowledge that these trees serve purposes beyond being a carbon sink. This study focuses on integrating border trees and home gardens as distinct land use classes in Indonesian Javanese agricultural land to assess their impact on carbon stock potential and biodiversity connections. The objective is to classify and quantify the tree composition of these classes, estimate their carbon stock potential, analyze plant species diversity, and identify the ecological connections between home gardens and field borders. To achieve this, high-resolution multispectral and Synthetic Aperture Radar images were used from four sampling areas covering 100 km2 each in Lamongan and Malang districts, East Java, Indonesia, for land cover/land use mapping. The land use function method was used to identify border trees and home gardens as separate land use classes. Carbon stock potential was estimated based on tree cover composition, while plant species diversity was analyzed through field surveys and farmer focus group discussions. Crops with border trees cover approximately 28% to 48% of the cropland area in the study sites, while home gardens represent about 74% to 85% of the settlement area. This suggests a potential to double tree presence in these sites by adopting border trees and home gardens practices across the entire area. The median tree cover ratio was around 27% for border trees and 33% for home gardens. This stratification approach identified 31% to 50% more carbon stock compared to calculations using standard classes. Furthermore, home gardens and border trees show a positive correlation with species richness, indicating their role as keepers of biodiversity. Therefore, home gardens and border trees could serve as a sustainability indicator for agricultural land in the Javanese farm system. This research contributes to sustainable agricultural practices and climate change mitigation. The stratification approach of identifying border trees and home gardens offers a cost-effective approach for the better computation of carbon stock and can lead to effective land use policies and conservation measures that promote ecological resilience. The study provides valuable insights for similar agricultural contexts worldwide, guiding efforts toward a more sustainable agricultural future.